The Emotional and Financial Impact of De-Platforming on Creators at the Margins - Carolina Are; Pam Briggs (Social Media + Society, 2023)
This study provides one of the first examples of de-platforming’s direct emotional and financial impact on Instagram and TikTok content creators at the margins. Both platforms provide significant opportunities toward creative and flexible work, allowing creators to maintain networks, promote work, express themselves and earn a living. However, their governance can severely disrupt certain forms of content creation, particularly for users who post online sex work and nude content. Through a qualitative survey, we gathered the experiences of 123 de-platformed Instagram and TikTok users who posted nude or sex work-related content. Our study provides crucial testimonies showing that the precarity of creator labor and platforms’ reliance on automated content moderation have negatively impacted creators’ well-being. Participants faced adverse psychological impacts resulting from job and income uncertainty, associated feelings of powerlessness, a loss of digital identity, and enforced isolation from a previously established social network. We conclude by providing platform governance recommendations based on these experiences.